Pengaruh Rekam Medis Elektronik Terhadap Efisiensi Pelayanan Kesehatan Poli Obgyn di RSU X - Syahla Reisya Nafiza; Annisa Ulfah (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Electron Medical Records are essential for Health Services to ensure more efficiency and effectiveness in serving patients, especially in OBGYN Polyclinics. Having an Electronic Medical Record can make work easier. The aim of this investigation is to find out how electronic medical records influence the efficiency of health services. The research method employed a quantitative analytical observation design method. The population used was 2 doctors and 6 nurses at the ob-gyn polyclinic. The results from questionnaire and simple linear regression test revealed that it has a strong correlation and the Pearson correlation value is 0.704 and also the variables x and y have a significant influence. Then, it is found that the test done through SPSS version 26 was declared valid and reliable